Parametric Optimization of Martensitic Stainless Steel 440 C in CNC Turning Using Box-Behnken and Response Surface Method - Dr. Hazem E. Radhi,Kadhim Saleh Marsool (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Stainless steels are used in a wide range of applications such as aerospace, marine, and automotive, because of maintaining their mechanical properties at high temperature and high corrosion resistivity. In industry in order to obtain high product quality, better productivity and extended tool life it is essential to optimize the machining parameters such as (cutting speed, feed and depth of cut). The main purpose of this paper is to study the effect of turning parameters of martensitic stainless steel (AISI440) in CNC turning under dry conditions on surface roughness, material removal rate and temperature. A box-behnken design (BBD) approach in response surface methodology (RSM) was used to model the surface roughness material removal rate and temperature as a response of the cutting parameters. Design expert (v12) was used to generate 17 experimental runs needed to develop and verify the empirical mathematical model of the roughness, material removal rate and temperature. The results indicated that the roughness is strongly affected by the feed rate, additionally the cutting speed is the main factor followed by feed rate Influences the material removal rate, whilst, the depth of cut followed by feed rate has great effect on temperature.